URGENCY OF DEFENDING THE COUNTRY IN THE DEVELOPMENT OF HIGHER EDUCATION CURRICULUM IN INDONESIA - Mahanani, Anajeng (Universitas Duta Bangsa Surakarta, 2022)
Higher Education has a big role in giving birth to the nation's generation that builds the country. Character formation is strongly influenced by learning in higher education. The country's development is strongly influenced by the spirit of the nation's generation that has a patriotic spirit. The quality of Human Resources, which only experienced strengthening in the academic field, cognitive abilities, is in fact not strong enough to build a sense of caring together to build the country. It is necessary to strengthen the character of defending the state, so that the love of the nation's generation for their country, encourages them to be able to work and build the nation. This simple study has great urgency in studying youth-based nation building. This article will discuss the role of the State Defense Curriculum in higher education and analyze the formulation of learning models that create students as a generation of patriotic characters. In the future, it is hoped that this simple study can provide an understanding for each higher education institution to be able to insert the spirit of state defense character development for students in every teaching and learning activity. This is collective homework.